ANALYSIS OF TAX BURDEN AND ITS RELEVANCE TO GOVERNMENT REGULATION NUMBER 23 YEAR 2018 FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSME) - Muhammad Alfiyan; Nur Arif Nugraha (Politeknik Keuangan Negara STAN, 2021)
The purpose of this study is to provide views of the implementation of the Government Regulation Number 23 Year 2018 (PP 23 of 2018) from the aspect of the tax burden. In the previous regulation, the equity principle actually contradicts with the convenience offered by the Government Regulation Number 46 Year 2013 (PP 46 of 2013). This is because PP 46 of 2013 imposes final income tax on the basis of taxation in the form of gross turnover. How does the government deal with this through PP 23 of 2018? Is PP 23 of 2018 relevant to be applied for MSMEs? The method used in this paper is descriptive by conducting comparative analysis. The results of the study stated that PP 23 of 2018 provides more opportunities for MSMEs to get tax incentives. In addition, PP 23 of 2018 is also more relevant in eroding the informal economy sector in Micro, Small, Medium Enterprises (MSMEs). PP 23 of 2018 allows MSMEs to use bookkeeping and MSMEs that used PP 23 of 2018 is given a certain period of time so that MSMEs cannot always employ PP 23 of 2018. Therefore, this regulation needs to include socialization related to bookkeeping and tax administration for MSMEs. Thus, the policy related to PP 23 of 2018 is correct. The results of this study are expected to be beneficial for the government, especially the Directorate General of Taxes.